2003
DOI: 10.1046/j.1472-8206.2003.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of vascular and platelet levels of nitric oxide and cyclic guanosine‐3′,5′‐monophosphate in cyclosporin A‐induced hypertensive rats

Abstract: The therapeutic use of the immunosuppressive agent cyclosporin A (CsA) is associated with arterial hypertension and increased risk of thromboembolism. Impaired endothelium-mediated relaxation is one of the main hypotheses explaining the CsA-induced vascular hyper-reactivity. Since nitric oxide (NO) modulates both vascular and platelet activity, we studied the effects of CsA on the levels of arterial and platelet NO as well as 3',5'-cyclic guanosine monophosphate (cGMP) levels which are influenced by NO. An ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…7,8,24 The reduction in aortic cNOS activity might be better explained by an effect on its complex enzymatic profile rather than by a reduction of L-arginine content or consumption, since previous studies have demonstrated that L-arginine supplementation was unable to prevent CsA-induced HT. 19,25 Thus, an effect on the enzymatic cofactors of cNOS may not be excluded, as already documented in other pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,24 The reduction in aortic cNOS activity might be better explained by an effect on its complex enzymatic profile rather than by a reduction of L-arginine content or consumption, since previous studies have demonstrated that L-arginine supplementation was unable to prevent CsA-induced HT. 19,25 Thus, an effect on the enzymatic cofactors of cNOS may not be excluded, as already documented in other pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Previous studies from our group, as well as from others, have shown a disequilibrium in the nitric oxide (NO)/cyclic guanosine-3=,5=-monophosphate (cGMP) system, which may contribute to the vascular hyperreactivity. 7,8 The NO system is essential to the relaxation of vascular smooth muscles cells (VSMC) and plays a pathophysiological role in reactive oxygen or nitrogen species (ROS) generation. 9 In addition, oxidative stress could also have a key role in CsA-associated cardiovascular toxicity.…”
Section: P Osttransplantation Hypertension (Ht)mentioning
confidence: 99%
“…We have previously reported that CsA administration is associated with a decrease of NO-cGMP contents (Santiago et al, 2003), that might be corrected by previous Is-5-Mn treatment . From the present data, it is reliable to consider that the CsA influence on left ventricle NE and E and aorta NE contents might have a NO deficiency dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) participates in the blood pressure control (Das and Kumar, 1995) and a pivotal role for a NO-cGMP (cyclic guanosine-3V,5V-monophosphate) pathway impairment has been gaining substantial attention during the last years (Marumo et al, 1995;Oriji and Keiser, 1998). However, despite widely studied, its contribution for the CsA-induced vascular dysfunction and hypertension, as well as the possible benefits of l-arginine supplementation (the most tested therapeutic intervention), remains incompletely elucidated (O'Neil et al, 1991;Stroes et al, 1997;Lassila et al, 2001;Santiago et al, 2003;El-Mas et al, 2004). In previous studies from our group, while l-arginine administration has shown inefficacy in preventing CsA-induced hypertension , the preliminary results with a different NO donor drug, the organic nitrate isosorbide 5-mononitrate (Is-5-Mn), have demonstrated promising results .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 During the last years several experimental and clinical studies, including some from our institute, have indicated a cardiovascular dysfunction in nitric oxide (NO) production as one important cause for the reduced relaxation leading to vascular hyperreactivity and increased peripheral resistance. 10,11 NO is the main endotheliumderived relaxing factor. Through its conversion to cyclic guanosine-3=, 5=-monophosphate (cGMP), it exerts vasodilatation, inhibition of vascular smooth muscle cell (VSMC) growth, and platelet inactivation, thus playing a pivotal role in cardiovascular physiology and pathophysiology, namely, arterial HT, atherosclerosis, and thrombosis.…”
Section: Espite the Introduction Of New Immuno-mentioning
confidence: 99%